Design and in Vitro Characterization of Tricyclic Benzodiazepine Derivatives as Potent and Selective Antileukemic Agents. Issue 1 (30th December 2020) - Mieczkowski, Adam; Frączyk, Tomasz; Psurski, Mateusz; Wińska, Patrycja; Siedlecki, Paweł; Dziełak, Monika; Trzybiński, Damian; Wilczek, Marcin; Bagiński, Maciej; Bieszczad, Bartosz; Woźniak, Krzysztof
Abstract: Currently available chemotherapeutic treatments for blood cancers (leukemia) usually have strong side effects. More selective, efficient, and less toxic anticancer agents are needed. We synthesized seven, new, optically pure (12a S )‐1, 3, 4, 12a‐tetrahydropyrazino[2, 1‐ c ][1, 4], 12(2 H, 11 H )‐dione derivatives and examined their cytotoxicity towards eight cancer cell lines, including urinary bladder (TCC‐SUP, UM‐UC‐3, KU‐19‐9), colon (LoVo), and breast (MCF‐7, MDA‐MB‐231) cancer representatives, as well as two leukemic cell lines (MV‐4‐11, CCRF‐CEM) and normal murine fibroblasts (Balb/3T3) as reference cell line. Three of the seven newly‐obtained compounds ((12a S )‐8‐bromo‐2‐(3‐phenylbenzoyl)‐1, 3, 4, 12a‐tetrahydropyrazino[2, 1‐ c ][1, 4], 12(2 H, 11 H )‐dione, (12a S )‐8, 9‐dimethoxy‐2‐(4‐phenylbenzoyl)‐1, 3, 4, 12a‐tetrahydropyrazino[2, 1‐ c ][1, 4], 12(2 H, 11 H )‐dione and (12a S )‐8‐nitro‐2‐(4‐phenylbenzoyl)‐1, 3, 4, 12a‐tetrahydropyrazino[2, 1‐ c ][1, 4], 12(2 H, 11 H )‐dione, showed enhanced activity and selectivity toward the leukemic MV‐4‐11 cell lines when compared to our previously reported compounds, with IC50 values in the range of 2.9–5.6 μM. Additionally, (12a S )‐9‐nitro‐2‐(4‐phenylbenzoyl)‐1, 3, 4, 12a‐tetrahydropyrazino[2, 1‐ c ][1, 4], 12(2 H, 11 H )‐dione exhibited a strong cytotoxic effect against the leukemic CCRF‐CEM (IC50 =6.1 μM) and MV‐4‐11 (IC50 =11.0 μM) cell lines, a moderate cytotoxic effect toward other tumor lines (IC50 =31.8–55.0 μM) and very weak cytotoxic effect toward the Balb/3T3 reference cell lines. Selected compounds were further evaluated for their potential to induce apoptotic cell death in MV‐4‐11 cells by measuring caspase‐3 activity. We also established the crystal structure of three products and investigated the effect of 22 derivatives of 1, 3, 4, 12a‐tetrahydropyrazino[2, 1‐ c ][1, 4], 12(2 H, 11 H )‐dione on the activity of the cancer‐associated enzyme autotaxin. All compounds proved to be weak inhibitors of autotaxin, although some ( R ) and ( S ) enantiomers had K i values of 10–19 μM. The obtained results showed that the tested compounds exhibited a selective antileukemic effect, which appeared not to be related directly to autotaxin. Molecular targets responsible for this effect remain to be identified. The newly obtained compounds can be used in the search for new, selective anticancer therapies. Abstract :